Failure analysis and experimental verification on the hydrogen-driven pitting corrosion of heat exchanger tube material. (July 2022) - Liu, Dong; Hu, Junying; Yuan, Xi; Zhou, Li; Zhong, Xiankang
Highlights: A steady passive film was formed on the surface of heat exchanger tube material specimen in the borate buffer solution. Hydrogen entering the heat exchanger tube material reduces the pitting corrosion resistance even in the presence of Cl − . Hydrogen increases in the content of metallic Fe and the OH – /O 2– ratio in the passive film. Hydrogen arises the density of cation vacancies and oxygen vacancies in the passive film, and thins the passive film. Abstract: Hydrogen provides a workable scheme for lightening heavy oil, but it also brings ammonium chloride (NH4 Cl) corrosion which could further lead to heat exchanger tubes leakage failure during hydrocracking. Moreover, the hydrogen entering steel may shorten the service life of the material. Therefore, the effect of hydrogen on failure of the heat exchanger tube material exposed to 3.5 wt% NH4 Cl solution analyzed and verified experimentally. The pitting susceptibility, semiconductive properties, surface morphologies, components of passive film were investigated using electrochemical techniques, surface characterization and Mott-Schottky analysis. The results show that hydrogen substantially decreases the charge transfer resistance and the pitting potential, and simultaneously increases the OH – /O 2– ratio and the densities of point defects in passive film. The results indicate that hydrogen increases the pitting corrosion susceptibility of specimens and weaken the pitting corrosion resistance of heat exchanger tube material during hydrocracking, thus the failure occurs.